QURAN AND SCIENCE ANALYTICAL STUDY OF STAGES OF HUMAN CREATION - Hafiz Munir Ahmad Cheema; Muhammad Waqas Mazhar (Journal of Religion and Society, 2025)
The stages of human creation are described in great detail and depth in the Holy Quran. These stages shed light on the physical, spiritual, and psychological aspects of man. The analysis of these stages also shows the compatibility with modern science and the scientific depth of the Qur'an. The beginning of the creation of man is from clay In the Qur'an, the origin of man is connected with clay: “He who created everything well and created the beginning of man's birth from clay”. This means that the elements of man's physical creation are taken from the earth. The biological process of human creation The Qur'an has clearly described the stages of creation of the human embryo: in these stages, spermatozoa, spermatozoa, bones and flesh, soul blowing (breathing of the soul), this stage distinguishes human beings from other creatures. It does, because the spiritual aspect is the source of man's consciousness, morality, and spiritual development. The process of man's creation continues even after birth, as stated in the Qur'an: “It is Allah who created you weak, then gave you strength after weakness, then after strength gave you weakness and old age." Man goes through the stages of childhood, youth, and old age. The stages of human creation in the Qur'an are remarkably consistent with modern biological science. The description of embryonic stages has been proven in modern times by ultrasound and research, which the Qur'an shows the truth and intellectual depth of these stages describe the evolution of human life, which reveals the power of a perfect creator. Modern science confirms these Quranic statements, which reveal the truthfulness of the Quran and the breadth of divine knowledge. Keywords: Qur'an, Remarkably, Consistent, Modern, Psychological, Aspects, Biological, Process